OPTIMALISASI PELAKSANAAN DIVERSI DALAM SISTEM PERADILAN PIDANA ANAK YANG BERORIENTASI PADA RESTORATIVE JUSTICE DI KOTA DENPASAR - Hariyanto, Diah Ratna Sari; Swardhana, Gde Made (Jurnal Legislasi Indonesia, 2021)
Abstract Diversion has become the starting point that legitimizes the settlement of criminal cases outside the judiciary in Indonesia. There are many benefits of diversion but it is very risky because it is not implemented optimally; therefore, the implementation and the constraints in the diversion application in Denpasar need to be studied and solutions to optimize the application to be sought. This research is empirical legal research. The results of the study show that the Departmental Police of Denpasar City, the Denpasar District Attorney, and the Denpasar District Court have attempted to implement diversion while remaining within the corridor of law, it shall only be implemented in respect of criminal acts of children who are punishable by imprisonment of under 7 years and not a recidivist. Obstacles encountered are the regulations regarding the ages of children based on the Law of SPPA, lack of coordination and supervision, law enforcers who have an inadequate understanding of the meaning and spirit of diversion, as well as lack of public awareness and understanding of the urgency of diversion. Optimization taken is reformulation of regulations, increased coordination, training, and socialization to law enforcers. Providing socialization and approaches to the community to increase understanding and awareness. Keywords: diversion, restorative justice, optimization.  Abstrak Diversi telah menjadi awal yang meletigitimasi penyelesaian kasus pidana di luar peradilan di Indonesia. Banyak manfaat yang diberikan melalui diversi namun sangat riskan tidak dilaksanakan secara optimal, sehingga perlu dikaji terkait pelaksanaan dan kendala penerapan diversi di Denpasar serta solusi untuk mengoptimalkan penerapan diversi. Penelitian ini adalah penelitian hukum empiris. Hasil studi menunjukkan bahwa Polresta Denpasar, Kejaksaan Negeri Denpasar, dan Pengadilan Negeri Denpasar telah mengupayakan diversi dengan tetap pada koridor hukum yakni hanya dapat dilakukan terhadap tindak pidana anak yang diancam dengan pidana penjara di bawah 7 tahun dan bukan residivis. Kendala yang dialami adalah pengaturan umur anak berdasarkan UU SPPA (substansi hukum), kurangnya koordinasi dan pengawasan (struktur hukum), dan masih bisa ditemukan penegak hukum yang tidak memahami makna dan spirit diversi, serta kurangnya kesadaran dan pemahaman masyarakat akan urgensi diversi (budaya hukum). Optimalisasi yang dapat dilakukan adalah dengan reformulasi aturan, meningkatkan koordinasi, pelatihan, serta sosialisasi ke penegak hukum. Mengadakan sosialisasi dan pendekatan ke masyarakat untuk meningkatan pemahaman dan kesadaran penyelesaikan kasus melalui diversi. Kata Kunci: diversi, keadilan restoratif, optimalisasi.